Assessing uncertainty associated with the monitoring and evaluation of spatially managed areas. (January 2015) - Stelzenmüller, Vanessa; Vega Fernández, Tomás; Cronin, Katherine; Röckmann, Christine; Pantazi, Maria; Vanaverbeke, Jan; Stamford, Tammy; Hostens, Kris; Pecceu, Ellen; Degraer, Steven; Buhl-Mortensen, Lene; Carlström, Julia; et al.
Abstract: Marine spatial planning (MSP) is advocated to support an ecosystem approach to marine management, as it allows consideration of multiple management objectives including marine conservation. The monitoring and evaluation of both implemented marine plans and the planning process itself is susceptible to various uncertainties. Here, uncertainties related to a stepwise monitoring and evaluation framework for spatially managed areas were characterised and quantified with the help of two modified and developed tools. In particular, Walker-type and pedigree matrices were utilised to assess both the sources and respective relative levels of uncertainty present in the assessment of nine European case studies that conducted a stepwise monitoring and evaluation process applying a common framework. Across the southern and northern European case studies major sources of uncertainty were found in relation to the knowledge base, management scenarios with related objectives and data availability. Although case studies made flexible use of the framework to account for the particularities of the local realms, the revealed pattern of associated uncertainty was highly consistent across the case studies. The scored pedigree matrices showed that the criteria 'stakeholder engagement' and 'cross validation' had greatest influence on the overall robustness of the case study assessments. The observed distribution of median pedigree scores was within acceptable ranges with respect to simulated possible score distributions. In addition, a sensitivity analysis revealed that the scoring of the pedigree criteria by five or more experts would result in less variable interquartile ranges of respective median scores. In conclusion, the developed complementary tools showed great flexibility in characterising and assessing uncertainty despite context-dependent differences among case studies such as geographical area, quality of available data, level of spatial management implementation or management objectives. Moreover, the obtained findings allow prioritising efforts and future research to support an iterative monitoring and evaluation of marine spatial plans. Highlights: Assessment of uncertainty in monitoring and evaluation of spatially managed areas. Assessment carried out in 9 European case studies. Outputs from two complementary approaches compared through Monte Carlo simulations. Uncertainty most frequently related to knowledge, data and scenario representation. Recommended to be made by at least 5 experts.